Registration of 'TN09‐008' Soybean Cyst Nematode–Resistant Cultivar. Issue 3 (21st June 2018) - Pantalone, Vince; Smallwood, Chris; Fallen, Ben; Hatcher, Catherine Nyinyi; Arelli, Prakash
Abstract : The conventional soybean [ Glycine max (L.) Merr.] line 'TN09‐008' (Reg. No. CV‐527, PI 686907) was released by University of Tennessee Agricultural Research in 2017 as a cultivar on the basis of its high seed yield potential in Tennessee and the southern region of the United States. TN09‐008 is resistant to HG types 1.2.5.7, 5.7, and 2.5.7 (races 2, 3, and 5, respectively) of soybean cyst nematode (SCN), resistant to stem canker, and shows field tolerance to sudden death syndrome and frogeye leaf spot. TN09‐008 is a maturity group V line with relative maturity of approximately 5.3. It will serve as an excellent parent line in breeding for broad resistance to SCN and several other important pathogens of soybean.